2019
DOI: 10.1093/cid/ciz432
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hemolytic Uremic Syndrome and Renal Replacement Therapy in Shiga Toxin–producing Escherichia coli–infected Children

Abstract: Background Shiga toxin–producing Escherichia coli (STEC) infections are leading causes of pediatric acute renal failure. Identifying hemolytic uremic syndrome (HUS) risk factors is needed to guide care. Methods We conducted a multicenter, historical cohort study to identify features associated with development of HUS (primary outcome) and need for renal replacement therapy (RRT) (secondary outcome) in STEC-infected children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
2
25
1
1
Order By: Relevance
“…From a clinical perspective, it is worth noting that diagnosis should be established as soon as possible so that the patient is admitted to the hospital for the timely implementation of the necessary support measures. 7,19 Both the strict and the usual definitions require the presence of anemia; [7][8][9][10][11] the absence of this condition was the most common cause of a wrong diagnosis across the series. A high hematocrit level indicates dehydration secondary to gastrointestinal losses, which has been observed in more than one third of patients at the time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, it is worth noting that diagnosis should be established as soon as possible so that the patient is admitted to the hospital for the timely implementation of the necessary support measures. 7,19 Both the strict and the usual definitions require the presence of anemia; [7][8][9][10][11] the absence of this condition was the most common cause of a wrong diagnosis across the series. A high hematocrit level indicates dehydration secondary to gastrointestinal losses, which has been observed in more than one third of patients at the time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…Desde el punto de vista clínico, es importante que el diagnóstico se establezca lo antes posible para indicar la hospitalización del paciente para que se instauren, de manera oportuna, las medidas de sostén necesarias. 7,19 Tanto la definición estricta como la habitual exigen la presencia de anemia, [7][8][9][10][11] su ausencia fue la causa más frecuente de falla diagnóstica en toda la serie. El hematocrito elevado refleja deshidratación secundaria a pérdidas gastrointestinales, hecho que se ha observado en más de un tercio de los pacientes al momento de la internación.…”
Section: Discussionunclassified
“…Several easily accessible clinical parameters have been evaluated or identified as prognostic markers in STEC-HUS. This includes parameters of thromboinflammation (e.g., leukocytosis [8][9][10], elevated D-dimers [11], complement activation [12]), urea [12], sodium [13], and lactate dehydrogenase (LDH) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, high hematocrit or hemoglobin levels as surrogate parameters of hemoconcentration have been associated with developing STEC-HUS or a more severe course of STEC-HUS [5,9,13,15,[17][18][19][20]. Based on these findings, Ardissino et al suggested a score (hemoglobin (g/dL) + 2 × creatinine (mg/dL) on admission) to identify patients at high risk for a severe course.…”
Section: Introductionmentioning
confidence: 99%